Primary Basic Subject by Clustering - Neelameghan, A. (Journal of Information and Knowledge, 1973)
The formation of Primary Basic Subjects by the Clustering mode is discussed. The result of Clustering is differentiated from certain other varieties of Primary Basic Subjects. The arrangement of Primary Basic Subjects formed by Clustering in a helpful sequence in the schedules of Basic Subjects of the Colon Classification is explained.